THE DIALOGUE – BASED ENGLISH WORKSHEET ENHANCES STUDENTS’ SPEAKING SKILLS - Nurlia, Nurlia; Dollah, Syarifuddin; Aeni, Nur (Universitas Negeri Makassar, 2025)
This research attempts to find out the use of dialogue-based English worksheets in fostering students' speaking skills. A quantitative approach with a pre-experimental research design was used in this study. The sample of the study consisted of 29 students of class X.E.3 who were selected using a cluster sampling technique. Pre- and post-tests were used to gather data. The t-test value was less than P (0.000 <0.05), showing that H0 is rejected and H1 is accepted. The data analysis results showed that the use of dialogue-based English worksheets significantly enhanced students' speaking abilities. Therefore, it can be said that the usage of dialogue-based English worksheets in class X.E.3 at SMAN 4 Maros is helpful in improving students' speaking abilities in English classes. By providing realistic conversation scenarios, dialog-based English worksheets help students improve their writing skills and allow them to practice writing in an authentic context. Through this exercise, students can develop confidence, communication skills, and a sense of self-esteem by using the right expressions and tone. In addition, these worksheets encourage active interaction between students and teachers so that students feel comfortable sharing their thoughts and spontaneous responses in English.